Efek Sari Buah Lemon pada Kekasaran Permukaan Restorasi Alkasit (Penelitian) - Anastasia Elsa; Steward Hadi (Jurnal Kedokteran Gigi Terpadu, 2019)
Background. Alkasite restoration materials are introduced as dental restoration materials to improve the function, shape and aesthetics of teeth. One of the aesthetic factors that needs to be considered is the smoothness of the surface of the restoration. The smoothness of restoration surface can be affected by various factors, one of which is the degradation due to low pH. Alkasite restoration materials are mentioned to have strong polymer bonds and fillers that can release hydroxide ions which are expected to neutralize acids. Objective. To determine the effect of lemon juice on the surface roughness of alkasite restorative materials. Methods. The samples used in this study were Cention N which was light-cured with LED light-curing unit. Samples were divided into 2 groups to be immersed in lemon juice and water  in  separate container for 1 hour 45 minutes. Surface roughness was measured before and after immersion using surface roughness tester (Surtronic S128 S-100 Series Handheld Roughness Tester). Results. The results showed significant changes in pH of lemon juice from 2,8 to 5,7 as well as average difference of surface roughness in the Alkasite restoration samples before and after immersion (ΔRa) in lemon juice (0.22680±0.022599 µm)  and  water (0.04600±0.032303 µm). Conclusion. This study showed that there was an increase  of lemon juice pH and Alkasite restoration surface roughness after immersion in lemon juice.